2006
DOI: 10.1111/j.1365-2621.2006.01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic composition of European cranberrybush (Viburnum opulus L.) berries and astringency removal of its commercial juice

Abstract: Phenolic composition of the European cranberrybush (ECB) (Viburnum opulus L.) juice was determined using high-performance liquid chromatography. The juice contained 2037 mg kg )1 chlorogenic acid, which was 54% of total phenolics, and several other phenolics such as (+)-catechin, ())-epicatechin, cyanidin-3glucoside, cyanidin-3-rutinoside and six different glucosides of quercetin. Because of its strong astringent taste, the juices were treated with various doses of two different types of activated carbons (Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(40 citation statements)
references
References 24 publications
8
31
0
1
Order By: Relevance
“…Its fruits are consumed fresh, in beverages and food preparations such as sauces, marmalades and jellies. They are reported to possess a high anti-oxidative effect, especially due to their high amount of polyphenolics, anthocyanins and ascorbic acid [13][14][15][16]. The bioactive phytocomponents of European cranberry bush fruits were also reported to possess antimicrobial, antidiabetic, antihypertensive and anti-inflammatory effects [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Its fruits are consumed fresh, in beverages and food preparations such as sauces, marmalades and jellies. They are reported to possess a high anti-oxidative effect, especially due to their high amount of polyphenolics, anthocyanins and ascorbic acid [13][14][15][16]. The bioactive phytocomponents of European cranberry bush fruits were also reported to possess antimicrobial, antidiabetic, antihypertensive and anti-inflammatory effects [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Viburnum opulus contain high level phenolic compounds such as hydroxybenzoic acids, tannins, flavonoids, anthocyanins, chlorogenic acid, catechin, epicatechin, cyanidin-3-glucoside, cyanidin-3-rutinoside and quercetin (Velioglu, Ekici, & Poyrazoglu, 2006;Perova, I. B., Zhogova,Cherkashin,Éller, &Ramenskaya, 2014).)…”
Section: Compositionmentioning
confidence: 99%
“…In an investigation to profile phenolic compounds in viburnum berries using high-performance liquid chromatography Velioglu et al, (2006) identified chlorogenic acid (upto 2037 mg/kg ), catechin, epicatechin, cyanidin-3-glucoside, cyanidin-3-rutinoside and different glucosides of quercetin and cyanidin derivatives (Velioglu, Ekici, & Poyrazoglu, 2006). Zakłos-Szyda 2019has identified and quantified the major phenolic compounds where they reported chlorogenic acid as main component.…”
Section: Compositionmentioning
confidence: 99%
“…ìåòîäàìè ÂÝAEÕ-ÌÑ è ßÌÐ èäåíòèôèöèðîâàëè öèàíèäèí-3ãëþêîçèä, öèàíèäèí-3-êñèëîçèëðóòèíîçèä è öèàíèäèí-3-àðàáèíîçèëãëþêîçèä.  äðóãèõ âèäàõ êàëèíû íàéäåíû öèàíèäèí-3-ñàìáóáèîçèä, öèàíèäèí-3-ãëþêîçèä, öèàíèäèí-3-ãàëàêòîçèä è öèàíèäèí-3-êñèëîçèëãàëàêòîçèä [10,11]. Òàêaeå èõ ìîaeíî îáúÿñíèòü óñëîâèÿìè ïðîèçðàñòàíèÿ, íàïðèìåð, ïî÷âåííûìè, ãåî-ãðàôè÷åñêèìè, ñòåïåíüþ çðåëîñòè ïëîäîâ âî âðåìÿ ñáîðà.…”
Section: ðåçóëüòàòû è èõ îáñóAeäåíèåunclassified